Brokerage in commercialised healthcare systems: A conceptual framework and empirical evidence from Uttar Pradesh. (April 2018) - Hunter, Benjamin M.
Abstract: In many contexts there are a range of individuals and organisations offering healthcare services that differ widely in cost, quality and outcomes. This complexity is exacerbated by processes of healthcare commercialisation. Yet reliable information on healthcare provision is often limited, and progress to and through the healthcare system may depend on knowledge drawn from prior experiences, social networks and the providers themselves. It is in these contexts that healthcare brokerage emerges and third-party actors facilitate access to healthcare. This article presents a novel framework for studying brokerage of access to healthcare, and empirical evidence on healthcare brokerage in urban slums in Lucknow, Uttar Pradesh. The framework comprises six areas of interest that have been derived from sociological and political science literature on brokerage. A framework approach was used to group observational and interview data into six framework charts (one for each area of interest) to facilitate close thematic analysis. A cadre of women in Lucknow's urban slums performed healthcare brokerage by encouraging use of particular healthcare services, organising travel, and mediating communications and fee negotiations with providers. The women emphasised their personal role in facilitating access to care and encouraged dependency on their services by withholding information from users. They received commission payments from healthcare programmes, and sometimes from users and hospitals as well, but were blamed for issues beyond their control. Disruption to their ability to facilitate low-cost healthcare meant some women lost their positions as brokers, while others adapted by leveraging old and new relationships with hospital managers. Brokerage analysis reveals how people capitalise on the complexity of healthcare systems by positioning themselves as intermediaries. Commercialised healthcare systems offer a fertile environment for such behaviours, which can undermine attainment of healthcare entitlements and exacerbate inequities in healthcare access. Highlights: Notes importance of third-party actors as mediators of healthcare access. Sets out a novel framework for healthcare brokerage analysis. Applies the framework to healthcare brokerage in Lucknow's urban slums. Emphasises the precarity and costs of brokerage, and its potential rewards. Discusses wider relevance and implications for equity of access to healthcare.